Hungarian EFL Students' Perspectives on Global Competence Development in a Thematic Language Course - Divéki, Rita; Harangozó, Eszter Lili (GILE Journal of Skills Development, 2024)
In today’s increasingly complex world, education must equip students to become engaged, globally competent citizens, who can solve both local and global issues and are ready to face the challenges of the 21st century. The goal of global competence is to address these demands by strengthening the necessary knowledge, skills and attitudes: a globally competent student can examine issues of global significance, understand other people’s perspectives, engage in appropriate and effective interactions with people from different cultural backgrounds, and act for collective well-being and sustainable development. In this framework, this case study aims to explore how a thematic language development seminar focussing on global content can contribute to developing second-year EFL students’ global competence and its perceived effectiveness. One group of students (N=18) from a prestigious Hungarian university was involved in the study, instructed by the first author. Data was collected over the course of the Spring 2023 semester from multiple data sources: student reflections after each thematic lesson, a beginning-of-the-term feedback sheet, an end-of-the-term feedback sheet, weekly student reflections, observation notes (by the second author) and reflective journals (by the first author). The findings emerging from this qualitative inquiry suggest that the students were satisfied with the course overall and could effectively gauge which global and language skills they developed during the course. These findings imply that designing courses with dual aims is both feasible and worthwhile, and with the help of regular reflection exercises, the students can be made aware of the development of their skills, leading to increased global awareness and satisfaction with the course.